2020
DOI: 10.3390/jmse8120979
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Hydrodynamic Responses to Atmospheric Systems with Different Scales: Impact of Cold Fronts vs. That of a Hurricane

Abstract: In this paper, subtidal responses of Barataria Bay to an atmospheric cold front in 2014 and Hurricane Barry of 2019 are studied. The cold fronts had shorter influencing periods (1 to 3 days), while Hurricane Barry had a much longer influencing period (about 1 week). Wind direction usually changes from southern quadrants to northern quadrants before and after a cold front’s passage. For a hurricane making its landfall at the norther Gulf of Mexico coast, wind variation is dependent on the location relative to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The wave energy in the south (S) was of similar magnitude to that generated by the CF along the coast (Figure 11c,h); the maximum H s was nearly 4 m. Thus, the amount of wave energy induced by the CF was similar to that generated by Harvey, excluding the highest waves of H s > 4 m before landfall, which lasted for 14 h (Figure 11b,g). Synoptic-scale cold fronts occur more frequently than tropical cyclones in the northwestern Gulf of Mexico [35], and these fronts significantly modulate the nearshore circulation [20,36]. In this study, we found that both extreme events intensified alongshore currents and induced highly energetic waves.…”
Section: Discussionsupporting
confidence: 47%
“…The wave energy in the south (S) was of similar magnitude to that generated by the CF along the coast (Figure 11c,h); the maximum H s was nearly 4 m. Thus, the amount of wave energy induced by the CF was similar to that generated by Harvey, excluding the highest waves of H s > 4 m before landfall, which lasted for 14 h (Figure 11b,g). Synoptic-scale cold fronts occur more frequently than tropical cyclones in the northwestern Gulf of Mexico [35], and these fronts significantly modulate the nearshore circulation [20,36]. In this study, we found that both extreme events intensified alongshore currents and induced highly energetic waves.…”
Section: Discussionsupporting
confidence: 47%
“…The multiscale, multiphysics nature of coastal ocean flows is attributed to various factors, and wind fields are among those that play an essential role. With the aid of FVCOM, a comparison study was made on effects from cold fronts in 2014 and Hurricane Barry in 2019 on flow patterns inside Barataria Bay [23]. In general, these fronts and the hurricane's wind fields exhibited distinct differences not only in temporal and spatial scales but also in directions.…”
Section: A Discussion Of the Collected Papersmentioning
confidence: 99%
“…Investigation of water flow through a total of nine tidal inlets of the Barataria Basin was conducted by Water Institute of the Gulf and Coastal Restoration and Protection Authority (CPRA) in 2019 by deploying fixed instruments at tidal inlets (Barataria Pass, Quatre Bayou Pass, and Fontanelle Pass) and conducting vessel-based surveys at all inlets for flow velocity measurements (15 January -26 September, 2019) available at CPRA Coastal Information Management System (Ramatchandirane et al, 2019). Meanwhile, the water volume flux through four tidal inlets (Caminada Pass, Barataria Pass, Pass Abel, and Quatre Bayou Pass) was estimated from a finite volume community ocean model (FVCOM) by integrating along channel velocity at different layers through the cross-sectional area and further validated with observational data collected in 2019 with more details documented in Huang and Li (2020).…”
Section: Water Flux During Hurricane Barrymentioning
confidence: 99%
“…During the study period (2019-2021), three hurricanes, namely, Barry in 2019, Zeta in 2020 and Ida in 2021 made landfall along the Louisiana coast and appeared to have the greatest impact on DOC distributions and carbon cycling in the Barataria Basin. Hurricane Barry made landfall as a Category 1 hurricane on Marsh Island, Louisiana with maximum reported storm-total rainfall of 0.58 m near Ragley, Louisiana (Huang and Li, 2020). A step increase in DOC concentration following the hurricane passage was mainly observed in Lake Salvador, Barataria and Terrebone bays (Figure 8), with elevated DOC concentrations (7.9-10.2 mg L -1 ) observed in the upper Barataria Basin; we further examine DOC fluxes from the bay into the shelf following the hurricane passage (section 3.4.3).…”
Section: Doc Response To Three Hurricane Passages -Barry Zeta and Idamentioning
confidence: 99%